(untitled) (Research, Society and Development, 2022)
Objective: To develop the epidemiological profile of Hepatitis B in the state of Pará from 2015 to 2020. Methods: An epidemiological, longitudinal, retrospective, analytical and exploratory study was carried out, based on a quantitative research, through the collection of data from the Department f Informatics of the Unified Health System (DATASUS) in the period between the years 2015 to 2020. Result: In the year 2015 to 2020, in th state of Pará, 170.967 cases of Hepatitis B were registered. The highest number occurred in the year 2014 with 4.785 records. According to age group, the most affected were between 40 and 59 years old, with 78.73 notifications. The number of cases was higher in relation to males, with 98.233 records. Regarding race, White women registered a greater number of cases, totaling 80.324. According to the distribution of cases, totaling 80.324. According to the distribution of cases by health regions, Metropolitan Region I showed the highest incidence, registering 1.273 cases. Regarding the etiologies, there was a greater number of registrations of the C Virus, with a total of 91.660 cases. Conclusion: According to the data presented by DATASUS, in the state of Pará, there were more than 30,000 registered cases of Hepatitis B, between the years 2015 to 2020, in 2019 there were 27,616 records, and a lower number in the year 2020 with 12,333 cases. The epidemiological profile shows that more male patients were affected, Caucasian and in the Metropolitan Region I. Regarding the age group, they were most affected between 40 and 59 years, and then between 20 and 39 years, with more cases in the adulthood, as this age group is more exposed to agglomerations, and thus, more susceptible to infections.